2021
DOI: 10.2147/jir.s319213
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pyroptosis-Related Indicators as Potential Biomarkers and Their Association with Severity in Patients with Liver Cirrhosis

Abstract: The diagnosis and management of liver cirrhosis remain challenging due to its diverse clinical manifestations and elusive severity evaluation. Pyroptosis, an identified inflammatory form of cell death, has recently been reported to participate in cirrhosis development. Nonetheless, the clinical significance of pyroptosis in liver cirrhosis remains largely unexplored. Patients and Methods: One hundred and fifty-one liver cirrhosis patients either alone or in combination with various complications and twenty-nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In addition, an in vitro mechanistic study showed that the pyroptosis products IL-1β and IL-18 regulate the activation of hepatic stellate cells (HSCs) and facilitate the development of liver fibrosis [ 14 ]. Notably, patients with liver cirrhosis also exhibited elevated levels of circulating GSDMD, IL-1β, and IL-18 in our previous clinical research [ 15 ]. Therefore, NLRP3 inflammasome-dependent pyroptosis may serve as a crucial mechanism for the development of liver injury and fibrosis.…”
Section: Introductionmentioning
confidence: 89%
“…In addition, an in vitro mechanistic study showed that the pyroptosis products IL-1β and IL-18 regulate the activation of hepatic stellate cells (HSCs) and facilitate the development of liver fibrosis [ 14 ]. Notably, patients with liver cirrhosis also exhibited elevated levels of circulating GSDMD, IL-1β, and IL-18 in our previous clinical research [ 15 ]. Therefore, NLRP3 inflammasome-dependent pyroptosis may serve as a crucial mechanism for the development of liver injury and fibrosis.…”
Section: Introductionmentioning
confidence: 89%
“…Research in this area is in demand and may lay the foundation for a better understanding of disease etiology. In addition to being an important mediator of pyroptotic cell death, GSDMD also holds potential as a circulating biomarker, as serum GSDMD levels are elevated in inflammatory diseases [55][56][57]. Whether GSDMD or other gasdermins can serve as circulating biomarkers of ongoing beta-cell pyroptosis should be investigated.…”
Section: Present and Future Perspectivesmentioning
confidence: 99%
“…GSDMD is the first molecule to be released into the extracellular environment and can trigger the release of IFN-β [29]. As the induction of pyroptosis diminishes, intracellular GSDMD expression and splicing cease, leading to a rapid decrease in total extracellular GSDMD levels, indicating a positive correlation between GSDMD and disease severity [30]. This characteristic makes GSDMD a potential biomarker for disease identification, early diagnosis, and the assessment of therapeutic efficacy and prognosis.…”
Section: The Process Of Pyroptosismentioning
confidence: 99%
“…Biomarkers, with their time-dependent effects, sensitivity, and early warning capabilities, have the potential to contribute to early disease diagnosis, reducing mortality rates, and improving survival and quality of life. Pyroptosis, a critical process in the occurrence and progression of major diseases [30][31][32], plays a significant role. GSDMD, as an effector molecule in pyroptosis, forms membrane pores and rapidly exits into the extracellular environment [13].…”
Section: Gsdmd As a Potential Biomarker For The Early Diagnosis Of In...mentioning
confidence: 99%
See 1 more Smart Citation